Cost evaluation of different household fuels and identification of the barriers for the choice of clean cooking fuels in India. (January 2020) - Sharma, Deepti; Ravindra, Khaiwal; Kaur, Manmeet; Prinja, Shankar; Mor, Suman
Graphical abstract: Highlights: Type of cooking fuel choice varies significantly with the monthly income of the family. Against the market price of $ 9.9/cylinder of LPG, the maximum willingness to pay is $ 4.1. Weekly cooking fuel cost was found to be highest ($ 3.1) for SBF followed by mixed fuel ($ 2.6) and LPG ($ 1.3). Distance from the LPG agency, the taste of meal and season are important determinant for the choice of household cooking fuel. There is a need to create awareness about the health effects of household air pollution. Abstract: The study aims to identify barriers for cleaner fuel alternatives and willingness to pay in Punjab, India. American Thoracic Society questionnaire was adopted as a study tool having additional questions on fuel subsidy and options, barriers for cleaner fuels choice, including the willingness to pay. Type of cooking fuel choice varies significantly with the monthly income of the family and 67% household uses solid biomass fuel (SBF) as a primary fuel, whereas 21% liquefied petroleum gas (LPG). Distance for the collection of clean fuel, the taste of meal and season were identified as important determinants for the choice of household cooking fuel. Weekly cooking fuel cost was found to be highest ($3.1) in SBF users followed by mixed ($2.6) and LPG ($1.3) fuel users. Against the market price of $9.9 per cylinder of LPG, the average willingness to pay was $4.1. The decision for cooking fuel is mostly taken by women (48%), although they prefer SBF for cooking and collect it (75%). As the SBF users were found ignorant about the associated non-communicable diseases, study urges to create awareness about the adverse health effects of household air pollution to increase the energy transition towards cleaner fuels.